Molecular switch behind adult stem cell quiescence in mouse stomach epithelium - Rocha, Andreia Sofia Batista (2021)
Ulcers are sores in the stomach lining that cause pain and discomfort that tend to lead to chronic inflammation of the stomach and consequently cancer. Stomach cancer is the second leading cause of death by cancer and the fifth most common malignancy in the world. Despite its frequency, early diagnose, premalignant state characterization and discovery of new treatments remain a challenge. Understanding how the stomach tissues behave in homeostasis is key to gain knowledge and overcome many of these roadblocks. Previous studies demonstrated that upon injury, base stem cells would exit quiescence and replenish the damaged tissue. It was then proposed that these were under the control of a reversible switch. Based on extensive injury-response data the CKI p57Kip2 appeared to be a promising candidate. During this study, organoids and mouse models were used. With the inducible Tet-On system, p57 was knocked into gastric organoids to allow for studies of its effects and reverse them in vitro. Through these organoids, niche requirement alterations, quiescence induction ability and pathway interactors were studied. In vivo knock out and knock in effects were assessed and compared to the in vitro tests. Other Cip/Kip family members were considered and finally p57 was overexpressed in an ectopic tissue in a similar way. Results showed that p57 can set stem cells into a quiescent state both in vitro and in vivo and has an impact on niche requirements. Pathway candidate IGF1R had a visible effect when inhibited on p57 overexpressing organoids. Short-term overexpression of Cip/Kip family members resulted in a mild phenotype of quiescence induction that needs to be confirmed in more extensive studies. Finally, although p57 was able to bring small intestinal cells into short-term quiescence, some challenges were faced. A new construct was designed to suppress these challenges, but further studies must be conducted to assure its success.